Departments in Crisis: What to do when the Department is Threatened - Craig D Hlavac (Academic Chairpersons Conference Proceedings, 2016)
Falling enrollments coupled with scarce resources have forced many institutions to urgently cut costs. While reducing discretionary spending may solve short-term financial shortfalls, institutions are more frequently considering academic reorganization or program elimination. Managing these situations as chairperson is not only challenging, but extremely stressful. This session will provide participants with practical, research-based advice for dealing with several exigent department-level situations. Crisis leadership, enrollment management, recruitment, program development, and discovering new revenue streams will be discussed.
Keywords: Crisis Leadership; Management; Academic Reorganization